Effects of a muscarinic type-2 antagonist on cardiorespiratory function and intestinal transit in horses anesthetized with halothane and xylazine - Teixeira Neto, Francisco José [UNESP]; McDonell, W. N.; Black, W. D.; Moraes, A. N.; Duronghphongtorn, S. (Amer Veterinary Medical Assoc, 2004)
Objective-To evaluate the cardiorespiratory and intestinal effects of the muscarinic type-2 (M-2) antagonist, methoctramine, in anesthetized horses.Animals-6 horses.Procedure-Horses were allocated to 2 treatments in a randomized complete block design. Anesthesia was maintained with halothane (1% end-tidal concentration) combined with a constant-rate infusion of xylazine hydrochloride (1 mg/kg/h, IV) and mechanical ventilation. Hemodynamic variables were monitored after induction of anesthesia and for 120 minutes after administration of methoctramine or saline (0.9% NaCl) solution (control treatment). Methoctramine was given at 10-minute intervals (10 mug/kg, IV) until heart rate (HR) increased at least 30% above baseline values or until a maximum cumulative dose of 30 mug/kg had been administered. Recovery characteristics, intestinal auscultation scores, and intestinal transit determined by use of chromium oxide were assessed during the postanesthetic period.Results-Methoctramine was given at a total cumulative dose of 30 mug/kg to 4 horses, whereas 2 horses received 10 mug/kg. Administration of methoctramine resulted in increases in HR, cardiac output, arterial blood pressure, and tissue oxygen delivery. Intestinal auscultation scores and intestinal transit time (interval to first and last detection of chromium oxide in the feces) did not differ between treatment groups.Conclusions and Clinical Relevance-Methoctramine improved hemodynamic function in horses anesthetized by use of halothane and xylazine without causing a clinically detectable delay in the return to normal intestinal motility during the postanesthetic period. Because of their selective positive chronotropic effects, M-2 antagonists may represent a safe alternative for treatment of horses with intraoperative bracycardia.